The Church of England's Pray One for Me intercessory prayer site: a virtual cathedral? - Tania ap Siôn (Journal of beliefs and values, 2016)
Over the past decade there has been a growing number of studies examining the prayer content of people's personal prayers left in intercessory church-related contexts. Since 2012, these studies have extended to include the cathedral intercessory prayer board and the online intercessory prayer site. Both "the cathedral" and "the online site" are distinctive contexts for intercessory prayer in terms of their openness and accessibility for a broad range of people, who are allowed to enter and use these prayer facilities. What is not known, however, is whether the cathedral prayer board and the online site are functioning in similar ways. This study presents an analysis of 500 prayers posted on the Church of England's "Pray One for Me" (POFM) website over a period of six months in 2012. The analysis employs the ap Siôn Analytic Framework for Intercessory Prayer (apSAFIP), which distinguishes among prayer intention, prayer reference, and prayer objective. The results of the analysis are compared with the results from recent cathedral studies employing the same analytic tool, and it is concluded that these two prayer contexts are functioning differently.